Coping with Evil in Religion and Culture : Case Studies - Doorn-Harder, Nelly van, 1956-; Minnema, Lourens (Currents of encounter ;, 2008)
The various Christian, Muslim, traditional (African), and secular (Western) ways of imagining and coping with evil collected in this volume have several things in common. The most crucial perhaps and certainly the most striking aspect is the problem of defining the nature or characteristics of evil as such. Some argue that evil has an essence that remains constant, whereas others say its interpretation depends on time and place. However much religious and secular interpretations of evil may have changed, the human search for sense and meaning never ends. Questions of whom to blame and whom to address?God, the devil, fate, bad luck, or humans?remain at the center of our explanations and our strategies to comprehend, define, counter, or process the evil we do and the evil done to us by people, God, nature, or accident. Using approaches from cultural anthropology, religious studies, theology, philosophy, psychology, and history, the contributors to this volume analyze how several religious and secular traditions imagine and cope with evil. Table of ContentsNelly van DOORN-HARDER and Lourens MINNEMA: The Problem of Defining EvilPart I: Evil in SpiritBirgit MEYER: Images of Evil in Popular Ghanaian ChristianityJacqueline BORSJE: Druids, Deer and?Words of Power?: Coming to Terms with Evil in Medieval IrelandMarthinus L. DANEEL: Coping with Wizardry in Zimbabwe in African Initiated Churches (AICs)Edien BARTELS: The Evil Comes from Outside: Evil within Religion as a Psychosocial Problem among Adolescent Moroccan Girls in the NetherlandsJ. Kwabena ASAMOAH-GYADU: Conquering Satan, Demons, Principalities, and Powers: Ghanaian Traditional and Christian Perspectives on Religion, Evil, and DeliverancePeter VERSTEEG and Andre DROOGERS: A Schema Repertoire Approach to Exorcism: Two Case Studies of Spiritual WarfareReender KRANENBORG: How 'Satanic? Is Satanism? A Normative DescriptionPart II: Evil in SocietyMartijn de KONING:?You Follow the Path of the Shaitan; We Try to Follow the Righteous Path?: Negotiating Evil in the Identity Construction of Young Moroccan-Dutch MuslimsNelly van DOORN-HARDER: Defining Evil to the Strengthen Islam: Muhammadiyah Ideologies of Gender and MarriageFrans WIJSSEN: Beyond Ujamaa: African Religion and Societal EvilPart III: Coping with EvilAndre LASCARIS: Religion and Evil from the Perspective of Mimetic TheoryLourens MINNEMA: Coping with Human Evil: Shakespeare?s Sense of Tragic RevengeEdwin KOSTER: The Power and Limits of Stories: On the Questions?How to Cope with Evil?? and?How to Avoid Evil?? Christiane TIETZ: Prayer as a Means of Coping with Evil: Approaches from the Perspective of Lutheran DogmaticsR. Ruard GANZEVOORT: Coping with Tragedy and MaliceGeneral IndexContributors to this Volume.